PENYULUHAN DAN DETEKSI DINI KANKER MULUT RAHIM DENGAN IVA TEST DI KELURAHAN BINTORO KABUPATEN JEMBER - Sugijati, Sugijati; Kiswati, Kiswati; Susilawati, Susilawati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
This community's devotion is called counseling and early detection of cervical cancer with an IVA Test in the bintoro district of Jember. This community devotion focusing on reproductive health in women in their reproductive age because at that age prone to reproductive health problems. One of the most common occurrences is cervical cancer, So it is necessary to improve information on cervical cancer and how to perform early detection of cervical cancer. In the district of Bintoro in Jember, at the time of a reproductive health examination for a woman of fertile age held by the midwives of puskesmas, from about 20 fertile woman mother, no mother has ever performed a cervical cancer examination due to lack of mother's insight on reproductive health and the prevention of cervical cancer. The goal of this community's devotion to improve mother's knowledge of cervical cancer. After the increased knowledge of cervical cancer were more fertile woman expect can keep reproductive health and increasing the awareness of fertile women to do early detection cervical cancer, one by giving reproductive health education by doing the IVA Test, Because the iva test is one of the simplest and most affordable cervical cancer screens or screenin and It can be performed at the sub district health services pratama (midwife practices independent) so it doesn't have to go to the hospital. From the results of evaluation of health education or counseling on cervical cancer, Before it was given counseling most of the mothers don’t know about cervical cancer including early detection of cervical cancer, only 25% of mothers understand about cervical cancer. After having been conducted health education or counseling on cervical cancer, 95% of mothers understand and agree to perform cervical cancer checks with IVA Test methods routinely in their area of residence